2018
DOI: 10.1111/jvh.13020
|View full text |Cite
|
Sign up to set email alerts
|

Improving hepatitis C direct‐acting antiviral access and uptake: A role for patient‐reported outcomes and lived experience

Abstract: Summary Hepatitis C virus contributes to substantial and growing mortality and morbidity. Fortunately, the advent of highly effective interferon‐free direct‐acting antiviral (DAA) medications and new diagnostic tests has the potential to dramatically alter the epidemiologic trajectory of hepatitis C, particularly for “hard‐to‐reach” populations. Treatment advances and cure will also likely alter the individual experience of living with hepatitis C. However, it is not yet known in what capacity. This paper prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…HCV infection is a public health concern, with over 185 million people infected around the world. About 1.8% of the United States population is positive for the antibody to HCV, with 74% chronically infected, of which, 25-35% will progress to liver cirrhosis associated with an estimated 8,000-10,000 deaths every year [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…HCV infection is a public health concern, with over 185 million people infected around the world. About 1.8% of the United States population is positive for the antibody to HCV, with 74% chronically infected, of which, 25-35% will progress to liver cirrhosis associated with an estimated 8,000-10,000 deaths every year [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…13 Lack of awareness of HCV status or available services, low perceived risk, or fear of HCV-related stigma and discrimination deter people from seeking HCV care, while time constraints and lack of specific HCV knowledge prevent providers from offering HCV care. [14][15][16][17] Madden et al 18 previously categorised reported barriers to HCV treatment as broadly based on personal, provider and system-level barriers. 18 An individual may be disinclined to access HCV treatment due to being asymptomatic (personal barrier), while also unable to receive treatment from their usual doctor (provider barrier) and further worried about experiencing stigma from a new provider (system-level barrier).…”
Section: Open Accessmentioning
confidence: 99%
“…However, there are limited data on PREs with DAA therapy among vulnerable populations. 4 In this study, we aimed to assess PREs in patients experiencing homelessness during HCV daa therapy in an integrated homeless shelter-based model of HCV care that was implemented following assessment of key stakeholders' perspectives. 2,5 1) associated with PREs were evaluated using univariable and multivariable logistic regression models.…”
Section: Introductionmentioning
confidence: 99%